Open government: socials rights on platform - Cipriano Rozados, Juan (Universidad Nacional del Litoral, 2019)
The succession of the diverse State paradigms, from its origins to the present day was more a thing of coexistence than a constant displacement of each previous one. But from mere coexistence up to real connivance there is always a long way, an integrative vision becomes indispensable in that journey. Nor Legal State was replaced by the emergence of Social State neither this last one disappeared completely when Neoliberal State became the universal model. The achievements in terms of recognition of the fundamentality of social rights are unquestionable and remain inmaculate. In Argentina, we presence a shift in the conception of the Public Administration. I propose myself to show how the Open Government paradigm, beyond standing as a platform in where social agents can now interact, has an horizon in the social rights. So as to consider Open Government as an alternative to make effective social rights in this XXI Century.